Barriers to Advance Care Planning in End-Stage Renal Disease: Who is to Blame, and What Can be Done?. Issue 2 (4th May 2018) - Kelley, Alan Taylor; Turner, Jeffrey; Doolittle, Benjamin
Abstract : Patients with end-stage renal disease experience significant mortality and morbidity, including cognitive decline. Advance care planning has been emphasized as a responsibility and priority of physicians caring for patients with chronic kidney disease in order to align with patient values before decision-making capacity is lost and to avoid suffering. This emphasis has proven ineffective, as illustrated in the case of a patient treated in our hospital. Is this ineffectiveness a consequence of failure in the courtroom or the clinic? Through our own experience we affirm what has been written before: that legal precedent favors intensive treatment in virtually all cases without 'clear and convincing evidence' of a patient's previously declared wishes to the contrary. Equally clear is that more than 20 years of support in the clinical literature suggesting advance care planning early in the course of disease can address challenges in the legal system for those lacking capacity. However, many physicians fail to recognize the need for advance care planning in a timely manner and lack the necessary training to provide it. The need for more training and new tools to recognize opportunities for advance care planning in daily practice remains unmet.